The Relationship Between Quadriceps Muscle Atrophy and Proprioception Function in Knee Osteoarthritis Patients - Susanti, Ayu; Wardhani, Rr. Indrayuni Lukitra; Pawana, I Putu Alit (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: Osteoarthritis of the knee (OA) patients can experience impaired proprioceptive function which causes instability, balance disorder and limited activity. Further analysis is needed to detect changes that occur. There are two methods to evaluate the speed and angle of a particular motion as an analysis of the function of proprioception, Time to Detect Passive Movements (TTDPM) and Joint Position Sense (JPS).Aim: To analyze the relationship between quadriceps muscle atrophy with proprioception in knee osteoarthritis patients.Methods: The design of this research is cross sectional analysis done in Dr. Soetomo General Hospital Surabaya, Indonesia. There were 25 knee OA patients (2 men and 23 women) with each subject had proprioception (JPS and TTDPM) function measured using isokinetics dynamometer on both sides of the knee.Results: This study shows the atrophic side had greater pain intensity and greater disturbance of proprioception. In addition, there were significant differences in JPS measurements at  angle of 30â°, and 60â° and TTDPM (p <0.05). No difference obtained at 45â° measurements angle.Conclusion: In this study, there was no association between quadriceps atrophy and function of proprioception in knee osteoarthritis patients. This was due to a number of confounding factors that cannot be controlled such as duration, difference in pain intensity, OA severity, physical activity before measurement, and fatigue which can affect proprioception function and bring misinterpretation on measurements.